2018
DOI: 10.1103/physrevb.97.054503
|View full text |Cite
|
Sign up to set email alerts
|

Muon spin rotation study of the topological superconductor SrxBi2Se3

Abstract: We report transverse-field (TF) muon spin rotation experiments on single crystals of the topological superconductor SrxBi2Se3 with nominal concentrations x = 0.15 and 0.18 (Tc ∼ 3 K). The TF spectra (B = 10 mT), measured after cooling to below Tc in field, did not show any additional damping of the muon precession signal due to the flux line lattice within the experimental uncertainty. This puts a lower bound on the magnetic penetration depth λ ≥ 2.3 µm. However, when we induce disorder in the vortex lattice b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
4
9
0
Order By: Relevance
“…Having in mind 100% SC volume fraction, the effective penetration depth, λ eff , at zero temperature is found to be 930(10) nm. Such a high value of λ eff was also estimated previously for other sister compounds, namely Cu and Sr doped Bi 2 Si 3 [24,50,51]. In view of the short coherence length and relatively large mean-free path l ∼ 50 nm [20], we can assume that Nb 0.25 Bi 2 Se 3 lies close to the clean limit.…”
Section: Resultssupporting
confidence: 80%
“…Having in mind 100% SC volume fraction, the effective penetration depth, λ eff , at zero temperature is found to be 930(10) nm. Such a high value of λ eff was also estimated previously for other sister compounds, namely Cu and Sr doped Bi 2 Si 3 [24,50,51]. In view of the short coherence length and relatively large mean-free path l ∼ 50 nm [20], we can assume that Nb 0.25 Bi 2 Se 3 lies close to the clean limit.…”
Section: Resultssupporting
confidence: 80%
“…This value will be reduced if the assumption of a fully superconducting sample is removed. Such a high value of λ ef f was also estimated previously for other sister compounds namely Cu and Sr doped Bi 2 Si 3 24,49,50 . In view of the short coherence length and relatively large l 20 , we can assume that Nb 0.25 Bi 2 Se 3 lies close to the clean limit.…”
Section: Figuresupporting
confidence: 83%
“…Intriguingly, it has been suggested that topological insulators of the Bi 2 Se 3 family could also be turned into topological superconductors [8]. Bulk doping by Cu [9][10][11][12][13], Sr [14][15][16][17], and Nb [18][19][20][21][22][23][24][25][26] has indeed led to the observation of (not necessarily topological) superconductivity in these materials. The mechanism driving the superconductivity is widely thought to be metal intercalation in the van der Waals gap between the quintuple layers forming the Bi 2 Se 3 structure [9].…”
Section: Introductionmentioning
confidence: 99%